Analisis Penerapan Industry 4.0 Dan Smart Manufacturing Terhadap Peningkatan Daya Saing Industri Melalui Pendekatan Integrated Industrial Systems - Jaka Wibowo (Journal of Collaborative Industrial Management (JCIM), 2026)
This study examines how the application of Industry 4.0 and smart manufacturing concepts contributes to industrial competitiveness enhancement through the Integrated Industrial Systems (IIS) approach. Employing a qualitative method with a multiple case study design, this research explores the dynamics of digital transformation across diverse manufacturing environments. Data were collected through in-depth interviews, field observations, and document analysis from various industrial stakeholders. The findings reveal that the success of Industry 4.0 implementation is not solely determined by technology adoption, but by the organization's ability to holistically integrate all industrial subsystems—from technological infrastructure, human resource capabilities, and innovation culture to collaborative ecosystems. The IIS approach proves effective as an analytical framework for understanding the complex interactions among variables in industrial transformation. This study recommends a phased implementation model that considers organizational readiness, innovation capacity, and alignment of digital strategy with long-term business objectives.